The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/jez.2464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethylenethiourea on metamorphosis and ovary development: A comparative study of three larval frogs

Abstract: Amphibian endocrine systems interact with each other during normal development.Interference with one of the endocrine systems may influence others. We studied the effect of a thyroid inhibitor (ethylenethiourea [ETU]) on metamorphosis and ovary development of three species, Sphaerotheca pashchima, Indosylvirana caesari, and Euphlyctis cyanophlyctis with different larval durations. We treated the tadpoles of these species with 50, 100, and 200 mg/L concentrations of ETU and studied their larval duration, size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, methimazole did not delay differentiation or inhibit metamorphosis; on the contrary, it was observed individual differences, with some tadpoles reaching metamorphosis while others have just reached premetamorphic states. Phuge et al (2021) reported the ethylenethiourea (a thyroid inhibitor) did not affect metamorphosis in Sphaerotheca pashchima and at lower concentrations stimulated metamorphosis in the anuran Indosylvirana caesari, and suggested differences in the larval development duration and sensitivity. Our experiments revealed that the stage at which exposure started had an impact on larval differentiation, since tadpoles exposed earlier to methimazole reached metamorphosis whereas tadpoles exposed later remain in prometamorphosis.…”
Section: Changes In Growth and Differentiation Ratesmentioning
confidence: 98%
“…Furthermore, methimazole did not delay differentiation or inhibit metamorphosis; on the contrary, it was observed individual differences, with some tadpoles reaching metamorphosis while others have just reached premetamorphic states. Phuge et al (2021) reported the ethylenethiourea (a thyroid inhibitor) did not affect metamorphosis in Sphaerotheca pashchima and at lower concentrations stimulated metamorphosis in the anuran Indosylvirana caesari, and suggested differences in the larval development duration and sensitivity. Our experiments revealed that the stage at which exposure started had an impact on larval differentiation, since tadpoles exposed earlier to methimazole reached metamorphosis whereas tadpoles exposed later remain in prometamorphosis.…”
Section: Changes In Growth and Differentiation Ratesmentioning
confidence: 98%